Fenomena Rasionalisasi Anggaran Pilkada yang Telah Disepakati: Studi Kasus di Kabupaten Ogan Komering Ulu Timur dan Kota Tidore Kepulauan - Faqih Mujahid; Susilo Harjono (Jurnal Adhyasta Pemilu, 2020)
The budget is one aspect that determines the quality of the implementation of regional head elections (Pilkada). The budget problem that arose in the 2020 Pilkada Concurrent was the rationalization carried out by the DPRD on the Pilkada budget which was contained in the Regional Grant Agreement Text (NPHD) even though the NPHD was signed by the Regional Head and Pilkada Organizer (KPU and Bawaslu) as evidence of the budget allocation agreement for the activities of organizing and supervising the Pilkada. Examples of this rationalization practice occurred in 2 (two) regions, namely Ogan Komering Ulu Timur District, South Sumatra Province, and Tidore Islands City, North Maluku Province. There are 2 (two) factors that give rise to the rationalization problem. First, poor communication between the elements of Pilkada organizers (KPU and Bawaslu) together with the Government and the DPRD, which led to a deadlock and made the Central Government have to step in to resolve it. Second, the classic problems experienced by Indonesia in matters of legal governance that are out of sync (disharmony between regulations) have an impact on the quality of Pilkada budget management. Several things that affect the quality of Pilkada budget management include: First, the practice of assigning staff in charge of the Pilkada budget both at the KPU and Bawaslu has not fulfilled the principle of "the right man on the right place". Second, there is regulatory disharmony, namely the law regulating the authority of the DPRD in carrying out its budgeting functions with the technical regulations of the Minister of Home Affairs regarding Pilkada budgeting. By using a qualitative descriptive research method, the author will examine the rationalization problem from the aspects of communication between institutions and regional election budget management. The author uses political communication theory and election budget management to formulate alternative solutions to these problems and provide a meeting point for Pilkada budget problems in these 2 (two) regions.